Synthesis of plus- and minus-strand RNA from poliovirion RNA template in vitro. - Hey, T D (1986)
The poliovirus RNA polymerase, 3Dpol, was used to synthesize RNA in vitro in the presence of a host factor preparation from uninfected HeLa cells and poliovirion RNA as the template. The transcription products included molecules approximately twice the length of the template, apparently resulting from hairpin formation and template-directed elongation, as previously reported (D. C. Young, D. M. Tuschall, and J. B. Flanegan, J. Virol. 54:256-264, 1985). Other polyadenylated template RNAs also yielded products that were twice the length of the template. The polarity of the products synthesized from plus-strand poliovirus RNA template was analyzed by Southern blotting using labeled product RNA to probe single-stranded poliovirus DNAs cloned into M13 vectors. The results demonstrated that host factor-mediated polymerase products contain newly synthesized plus-strand sequences as well as the expected minus-strand sequences. Polymerase products primed with oligo(U) were all of minus-strand polarity.